2017
DOI: 10.1007/s00414-017-1541-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and identification of eight designer benzodiazepine metabolites by incubation with human liver microsomes and analysis by a triple quadrupole mass spectrometer

Abstract: Designer benzodiazepines (DBZDs) have become of particular importance in the past few years. The metabolite monitoring of DBZD in biological fluids could be of great interest in clinical and forensic toxicology. However, DBZD metabolites are not known or not commercially available. The identification of some DBZD metabolites has been mostly explored by self-administration studies or by in vitro studies followed by high-resolution mass spectrometry. The question arose whether a unit resolution instrument could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…However, since only 1 of the 2 flubromazolam glucuronide isomers (isomer‐1) was detected in all patient samples, separation of these analytes is not that important since the preferred analytical target metabolite should be isomer‐1.The product ion spectrum for flubromazolam hydroxy metabolite isomer‐1 did not include a water loss from the [M + H + ] precursor ion. Previous studies have suggested that hydroxylation of midazolam and flubromazolam takes place on the methyl part of the triazole ring (α‐hydroxy) and the diazepine ring (4‐hydroxy). This in combination with the proposed structure of the product ions with m/z 333.0033 and 317.0084 suggest that hydroxylation of flubromazolam isomer‐1 most likely occurred on the diazepine ring.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, since only 1 of the 2 flubromazolam glucuronide isomers (isomer‐1) was detected in all patient samples, separation of these analytes is not that important since the preferred analytical target metabolite should be isomer‐1.The product ion spectrum for flubromazolam hydroxy metabolite isomer‐1 did not include a water loss from the [M + H + ] precursor ion. Previous studies have suggested that hydroxylation of midazolam and flubromazolam takes place on the methyl part of the triazole ring (α‐hydroxy) and the diazepine ring (4‐hydroxy). This in combination with the proposed structure of the product ions with m/z 333.0033 and 317.0084 suggest that hydroxylation of flubromazolam isomer‐1 most likely occurred on the diazepine ring.…”
Section: Discussionsupporting
confidence: 84%
“…To improve the detection of designer benzodiazepines, several studies have been undertaken to determine their metabolic patterns both in vitro and in vivo . Accordingly, studies have elucidated the metabolic profiles of flubromazolam, whereas no metabolites have been reported for pyrazolam . Nevertheless, in a bioanalytical study of designer benzodiazepines, a higher immunoassay test response than that expected from the concentration of parent compound was found for urine samples collected in pyrazolam intoxication cases, suggesting cross‐reactivity of the antibodies with metabolites of pyrazolam …”
Section: Introductionmentioning
confidence: 99%
“…Metabolic profile determination using human liver microsomes (HLM) is now routinely employed for studies involving various emerging therapeutic and novel psychoactive substances, including designer opioids . Understanding of metabolic profiles allows for increased windows of detection through the identification of primary and secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic pathways for benzodiazepines are fairly similar (Figures 3 and 4) and this allows metabolites to be predicted and actively searched for when analyzing samples using techniques such as LC-MS. 157,162 As a result of the aforementioned similar metabolic pathways, care must be taken when interpreting the apparent presence of a metabolite. For example, diclazepam is metabolised to lorazepam, lormetazepam, and delorazepam which are all prescription drugs.…”
Section: Tography-time Of Flight-mass Spectrometry (Lc-tof-ms) Currentlymentioning
confidence: 99%